Prevention of Stunting with the Edu-1000 Application in Pregnant and Breastfeeding Women in Kupang District - Bringiwatty Batbual; Wanti; Demsa Simbolon; Fransiskus Salesius Onggang; Melinda Rosita Wariyaka; Oklan B. T. Liunokas; Sabinus Bungaama Kedang (Jurnal Penelitian Pendidikan IPA, 2024)
The prevalence of stunting has decreased compared to the previous 2 years. However, this reduction still does not meet WHO's target, namely the prevalence of stunting <20%, while the prevalence of stunting in Indonesia in 15 provinces is still above 20%.  The aim of this research is to analyze stunting prevention with the edu-1000 first day of birth application in pregnant women and breastfeeding mothers in Kupang district. method. The research design used in this research is "one groups pretest-posttest design", Results: The level of knowledge of pregnant women and breastfeeding mothers is very good, the majority of respondents have very good skills, namely 25 people (50%). Based on the results of data analysis, there is an influence between respondents' knowledge about stunting on prevention attitudes as shown by (p-value 0.00 < 0.005), there is an influence between respondents' knowledge about stunting on prevention skills as shown by p-value 0.02 < 0.005. Conclusion. Prevention of stunting with the edu-1000 the First 1000 days life application can influence the incidence of stunting in pregnant women and breastfeeding mothers in Kupang district.